Co-occurrence of bacteria and viruses and serotype distribution of Streptococcus pneumoniae in the nasopharynx of Tanzanian children below 2 years of age following introduction of the PCV13 - Emgård, Matilda; Andersson, Maria; Gonzales-Siles, Lucia; Msuya, Sia E.; Nyombi, Balthazar M.; Nordén, Rickard; Muro, Florida; Lindh, Magnus; Andersson, Rune; Skovbjerg, Susann (Frontiers in Public Health, 2024)
Introduction Pneumococcal conjugate vaccines have reduced severe disease attributed to vaccine-type pneumococci in children. However, the effect is dependent on serotype distribution in the population and disease development may be influenced by co-occurrence of viral and bacterial pathogens in the nasopharynx. Methods Following introduction of the 13-valent pneumococcal conjugate vaccine (PCV13) in Tanzania we performed repeated cross-sectional surveys, including 775 children below 2 years of age attending primary healthcare centers. All children were sampled from nasopharynx and pneumococci were detected by single-target PCR. Pneumococcal serotypes/groups and presence of viruses and other bacteria were determined by two multiplex PCR assays. Results The prevalence of PCV13 vaccine-type pneumococci decreased by 50%, but residual vaccine-types were still detected in 21% of the children 2 years after PCV13 introduction. An increase in the non-vaccine-type 15 BC was observed. Pneumococci were often co-occurring with Haemophilus influenzae, and detection of rhino/enterovirus was associated with higher pneumococcal load. Discussion We conclude that presence of residual vaccine-type and emerging non-vaccine-type pneumococci in Tanzanian children demand continued pneumococcal surveillance. High co-occurrence of viral and bacterial pathogens may contribute to the disease burden and indicate the need of multiple public health interventions to improve child health in Tanzania.